Responsibilities of certified Public Accountants in Business Accounting Systems Perspective in Fighting Against Corruption - Pardi, Pardi (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
Corruption  usually  happened  in  accountancy  sector is  that accountant  receive such as fee or present from the client because of their jobs. (according to the will of the client). Accountants only receive a fee or reward that is not much (small) but can cause major corruption in the business  world, corruption in the accounting services sector is also give  a very  high  and  low  impact  on  tax  revenues.  This  resulted  in  the  public accounting profession in the public for  its image as the offense of public harm. The  purpose  of  this  study  were  (1)  to  describe  the  role  of  Certified  Public Accountants  in  the  perspective  of  the  business  accounting  system  for  combating corruption.  (2)  to  describe  a  form  of  misconduct  in  the  practice  of  Certified  Public Accountants.  (3)  to  determine  the  professions  commitment  to  eradicate  corruption  in the Public Accountants. This  type  of  research  is  descriptive  research.  The  research  site  is  in  the  public accounting  firm  tin  Surakarta,  Manufacturing  in Surakarta,  Tax  Office  and  the  Public in Surakarta . The type of data is primary data. Data collection techniques in the study were interviews, observation and literature study,  whereas the data analysis technique is interactive analysis. The  results  showed  that  (1)  Certified  Public  Accountants  has  an  active  and  a passive  role  in  combating  corruption.  That  role  effectively  because  it  is  supported  by the  components  of  the  legal  system  consisting  of  structural  components,  and  cultural substance (2) the offense in the practice of Certified Public Accountants, among others, (a) report the value of income is much lower than the actual, (b) tax consultant assisted the  company  of  a  public  accounting  firm  to  change  the financial  statements  for  the companys  operating  expenses  could  be  made  much  larger than  the  actual,  (c)  the taxpayer or the tax that the company bribed officials are not tax-deductible value of the investigation and audit of financial statements, (d) tax payer usually give message to the public accountant office that the operational costs can be neatly arranged in such a way that  the  company  is  only  subject  to  the  tax  rate  low  (3)  The  commitment  of  public accountants  in fighting  against corruption  is  the  participation  of    IAI  in G20 group, update competencies in enhancing professionalism in order to meet the needs of service users  and  create  a  strategic  step  toward  uniformity  in  the  language  of  accounting  for financial reporting in the private sector in Indonesia